2022
DOI: 10.3389/fmicb.2021.801091
|View full text |Cite
|
Sign up to set email alerts
|

Myxococcus xanthus R31 Suppresses Tomato Bacterial Wilt by Inhibiting the Pathogen Ralstonia solanacearum With Secreted Proteins

Abstract: The pathogenic bacterium Ralstonia solanacearum caused tomato bacterial wilt (TBW), a destructive soil-borne disease worldwide. There is an urgent need to develop effective control methods. Myxobacteria are microbial predators and are widely distributed in the soil. Compared with other biocontrol bacteria that produce antibacterial substances, the myxobacteria have great potential for biocontrol. This study reports a strain of Myxococcus xanthus R31 that exhibits high antagonistic activity to R. solanacearum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…A higher relative abundance of K05998 (pseudomonalisin [EC:3.4.21.100], peptidases, and inhibitors) was found in RH. Peptidases have been reported to be potential biocontrol factors participating in the predation of Myxococcus xanthus on R. solanacearum (Dong et al, 2022 ; Figure 6B ). An important differential pathway worth noting is “Quorum sensing,” which was found to be significantly enriched in the diseased rhizosphere ( Figure 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…A higher relative abundance of K05998 (pseudomonalisin [EC:3.4.21.100], peptidases, and inhibitors) was found in RH. Peptidases have been reported to be potential biocontrol factors participating in the predation of Myxococcus xanthus on R. solanacearum (Dong et al, 2022 ; Figure 6B ). An important differential pathway worth noting is “Quorum sensing,” which was found to be significantly enriched in the diseased rhizosphere ( Figure 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…A predation assay was performed on TPM plates (10 mM Tris-HCl (pH 7.6), 1 mM KPO 4 pH 7.6, 8 mM MgSO 4 , 1.5% agar) using the colony-induced predation method as described [ 36 , 37 ]. Overnight cultures of P. aeruginosa PAO1 were resuspended in an LB medium and cultured to the mid-exponential phase.…”
Section: Methodsmentioning
confidence: 99%
“…It was later found that myxobacteria could also be used in the control of plant bacterial diseases with remarkable results. Myxococcus xanthus R31 showed a good biological control effect on tomato bacterial wilt [9]. Moreover, the secondary metabolites of myxobacteria cannot be ignored to inhibit plant diseases, which play an important role in agricultural applications.…”
Section: In Agriculturementioning
confidence: 99%